1995
DOI: 10.1161/01.res.77.2.361
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Voltage-Gated K + Channel Subunits in Adult Rat Heart

Abstract: Polyclonal antibodies against each of the K+ channel subunits (Kv1.2, Kv1.4, Kv1.5, Kv2.1, and Kv4.2) shown previously to be expressed in adult rat heart at the mRNA level were used to examine the distributions of these K+ channel subunits in adult rat atrial and ventricular membranes. Immunohistochemistry on isolated adult rat ventricular myocytes revealed strong labeling with the anti-Kv4.2 and anti-Kv1.2 antibodies. Although somewhat weaker (than with anti-Kv1.2 or anti-Kv4.2), positive staining was also ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
147
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(162 citation statements)
references
References 30 publications
12
147
3
Order By: Relevance
“…The molecular identity of I to is species-specific. In ferret and rat hearts the molecular correlate of I to is both Kv4.2 and Kv4.3 (24,25), whereas in the human and canine hearts Kv4.3 is the dominant isoform (26,27). Ion channels of the Shal family, Kv4.2 and Kv4.3, are regulated by a variety of extracellular factors including inhibition via ā£ 1 -adrenergic, muscarinic, endothelin, and angiotensin receptors (15, 16, 29 -32).…”
mentioning
confidence: 99%
“…The molecular identity of I to is species-specific. In ferret and rat hearts the molecular correlate of I to is both Kv4.2 and Kv4.3 (24,25), whereas in the human and canine hearts Kv4.3 is the dominant isoform (26,27). Ion channels of the Shal family, Kv4.2 and Kv4.3, are regulated by a variety of extracellular factors including inhibition via ā£ 1 -adrenergic, muscarinic, endothelin, and angiotensin receptors (15, 16, 29 -32).…”
mentioning
confidence: 99%
“…Kv2.1, a slow-inactivating delayed rectifier channel (16), although being widely distributed in the central nervous system, mainly on postsynaptic structures (17,18), is the prevalent Kv channel in neuroendocrine and endocrine cells (19,20). It was shown that the Kv2.1 current repolarizes ā¤-cell action potentials during a glucose stimulus to limit Ca 2Ļ© entry and insulin secretion (21).…”
mentioning
confidence: 99%
“…There are >15 different potassium channel genes that have been quantitatively demonstrated to exist in rat atrial and ventricular muscles, with Kcna2, kv1.4, kv1.5, kv2.1, and kv4.2 being expressed at significant levels 7, 27. Western blot analyses of atrial and ventricular membrane proteins confirmed the presence of Kcna2 at 75Ā kDa in adult rat heart membranes 8. Furthermore, Kcna2 has also been observed in human ventricular tissue 5.…”
Section: Discussionmentioning
confidence: 86%
“…There is direct evidence showing that the I Ks is generated by Kcna2 in Xenopus oocytes, rabbit vascular myocytes, pulmonary arterial smooth muscle cells, rat mesenteric artery smooth muscle cells, and canine colonic circular smooth muscles 29, 30, 31, 32, 33. Specifically, Kcna2 was demonstrated to contribute to the I Ks, rather than the transient outward potassium current, in adult rat myocytes 8. We verified that Kcna2 channels encode I Ks , as shown in FigureĀ S5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation